Phosphatidylethanolamine made in the inner mitochondrial membrane is essential for yeast cytochrome bc 1 complex function - Elizabeth Calzada (Nature Portfolio, 2019)
Phosphatidylethanolamine (PE) is synthesized by four separate pathways, although surprisingly, perturbing mitochondrial PE synthesis compromises mitochondrial function. Here, the authors show that mitochondrial PE synthesis is required for Complex III function and challenge PE trafficking dogma.